2020
DOI: 10.3390/en13226005
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Performance Prediction Equation for a Modular Ground Heat Exchanger

Abstract: Although ground source heat pump (GSHP) systems are more efficient than conventional air source heat pump (ASHP) systems, their high initial investment cost makes it difficult to introduce them into small buildings. Therefore, the development of a method for reducing the installation costs of GSHPs for small buildings is essential. This study proposes a modular ground heat exchanger (GHX) for cost reduction and an improved workability of GSHPs. In addition, a numerical model was constructed for the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Numerical Study Nam et al [6] Development of a numerical model to predict heat exchange rates of a GSHP system Congedo et al [7] CFD simulations of horizontal GHXs, comparison of different configurations Dasare and Saha [8] Numerical study of horizontal GHX for high energy demand applications Oh et al [18] Performance analysis of a low-depth unit-type GHX using numerical simulation Yoon et al [14] Thermal efficiency evaluation and cost analysis of different types of GHXs in energy piles Gabrielli and Bottarelli [19] Financial and economic analysis of ground-coupled HP using shallow GHX Selamat et al [9] Numerical study of horizontal GHXs for design optimization through CFD simulation Habibi and Hakkaki-Fard [20] Evaluation and improvement of thermal performance of different types of horizontal GHXs based on techno-economic analysis Saeidi et al [21] Numerical simulation of a novel spiral type GHX for enhancing heat transfer performance of geothermal HP Kim and Nam [10] Development of performance prediction equation for a modular GHX Experimental Study Shonder et al [22] A new comparison of design methods for vertical GHXs for residential applications Esen et al [11] Energy and exergy analysis of a ground-coupled HP system with two horizontal GHXs Luo et al [12] Thermal performance and economic evaluation of double U-tube borehole heat exchanger with three different borehole diameters Yoon et al [23] Evaluation of thermal efficiency in different types of horizontal GHXs Luo et al [13] Thermo-economic analysis of four different types of GHXs in energy piles Sipio and Bertermann [15] Factors influencing thermal efficiency of horizontal GHXs Kayaci and Demir [24] Long time performance analysis of GSHPs for space heating and cooling applications based on thermo-economic optimization criteria Arif et al [16] GSHP with horizontal GHXs for space cooling in hot tropical climates Kim et al [17] Analysis on the effect of performance factor on GSHP system…”
Section: Year Author(s) Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical Study Nam et al [6] Development of a numerical model to predict heat exchange rates of a GSHP system Congedo et al [7] CFD simulations of horizontal GHXs, comparison of different configurations Dasare and Saha [8] Numerical study of horizontal GHX for high energy demand applications Oh et al [18] Performance analysis of a low-depth unit-type GHX using numerical simulation Yoon et al [14] Thermal efficiency evaluation and cost analysis of different types of GHXs in energy piles Gabrielli and Bottarelli [19] Financial and economic analysis of ground-coupled HP using shallow GHX Selamat et al [9] Numerical study of horizontal GHXs for design optimization through CFD simulation Habibi and Hakkaki-Fard [20] Evaluation and improvement of thermal performance of different types of horizontal GHXs based on techno-economic analysis Saeidi et al [21] Numerical simulation of a novel spiral type GHX for enhancing heat transfer performance of geothermal HP Kim and Nam [10] Development of performance prediction equation for a modular GHX Experimental Study Shonder et al [22] A new comparison of design methods for vertical GHXs for residential applications Esen et al [11] Energy and exergy analysis of a ground-coupled HP system with two horizontal GHXs Luo et al [12] Thermal performance and economic evaluation of double U-tube borehole heat exchanger with three different borehole diameters Yoon et al [23] Evaluation of thermal efficiency in different types of horizontal GHXs Luo et al [13] Thermo-economic analysis of four different types of GHXs in energy piles Sipio and Bertermann [15] Factors influencing thermal efficiency of horizontal GHXs Kayaci and Demir [24] Long time performance analysis of GSHPs for space heating and cooling applications based on thermo-economic optimization criteria Arif et al [16] GSHP with horizontal GHXs for space cooling in hot tropical climates Kim et al [17] Analysis on the effect of performance factor on GSHP system…”
Section: Year Author(s) Descriptionmentioning
confidence: 99%
“…Selamat et al [9] studied the optimization of a horizontal GHX using different layouts and pipe materials, based on computational fluid dynamics (CFD) simulation. Kim and Nam [10] proposed a new modular GHX and developed a performance prediction equation for it through a numerical study. The results showed that the coefficients of variation of the root mean square error (RMSE) of the ground temperature model and entering water temperature (EWT) model were 5.2% and 1.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They also developed simulation models for GSHP systems with short helical borehole GHEs and predicted the performance [3]. Kim and Nam et al proposed a modular GHE and developed a performance prediction model [4]. They also installed modular GHEs and evaluated their heat extraction and injection performance [5].…”
Section: Introductionmentioning
confidence: 99%